DESAIN DAN FABRIKASI MESIN PELIPAT KEMASAN MAKANAN TIPE IVORY PAPERBOARD SINGLE COMPARTMENT - Marcelinus Adityapratama Soesilo (2024)
Paper - based food packaging is widely recycled so it is cheap and easy to obtain. Catering industries use this packaging as food containers, but the folding process still use human labor. Forming Lunchbox Machine is a semi - automatic paper food packaging folding machine based on a microcontroller and temperature control. This machine uses Arduino Uno as an automatic system and can be operated by one person, reducing labor and increasing packaging folding efficiency. The methods used in this research include design and fabrication. The machine made has dimensions of 510×510×772 mm. With the main components namely the frame, upper mold, and lower mold. Total cost of production for this machine is Rp. 2.828.500. The machine can operate optimally at a temperature of 210℃ with a press time of 15 seconds.